(3QSGdI COHjIs - (3YHO Gddg Hf GdebaY , GHf GdebaY , CHh YeQ,J (B142 (3g` s
(3ChdgG (B:s
(3Ef dcd EfSGf MGLI hEdi cd MGLI SHjd EdN s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B156s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B470 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2417) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdCOHs